BOSHLANGICH SINF O‘QUVCHILARI NUTQINI O‘STIRISH YO‘LLARI VA USULLARI - Babasheva, G.B. (SCIENCE and SOCIETY, 2023)
The article talks about the ways and methods of developing the speech of elementary school students. Several methods are illustrated as examples.